Plasmon-enhanced fluorescence for biophotonics and bio-analytical applications - Dasgupta, Souradip; Ray, Krishanu (Frontiers in Chemistry, 2024)
Fluorescence spectroscopy aids as an ultra-sensitive sophisticated tool wherein background noises which serves as a major impediment to the detection of the desired signals can be safely avoided for detections down to the single-molecule levels. One such way of bypassing background noise is Plasmon-enhanced fluorescence (PEF) where the interactions of fluorophores at the surface of metals or plasmonic nanoparticles is probed. The underlying condition being a significant spectral overlap between the localized surface plasmon resonance (LSPR) of the nanoparticle and the absorption or emission spectra of the fluorophore. The rationale being the coupling of the excited state of the fluorophore with the localized surface plasmon leads to an augmented emission owing to local field enhancement. It is manifested in enhanced quantum yields concurrent with a decrease in fluorescence lifetimes owing to an increase in radiative rate constants. This improvement in detection provided by PEF allows a significant scope of expansion in the domain of weakly emitting fluorophores which otherwise would have remained unperceivable. The concept of coupling of weak emitters with plasmons can bypass the problems of photobleaching, opening up avenues of imaging with significantly higher sensitivity and improved resolution. Furthermore, amplification of the emission signal by coupling of free electrons of the metal nanoparticles with the electrons of the fluorophore provides ample opportunities in achieving lower detection limits that is involved in biological imaging and molecular sensing. One avenue that has attracted fair share of attraction in the last few years is fast, label-free detection of bio-analytes at physiological conditions using plasmonic nanoparticles for point-of-care analysis. This review focusses on the applications of plasmonic nanomaterials in the field of biosensing, imaging with a brief introduction on the different aspects of localized surface plasmon resonance (LSPR) and fabrication techniques.